Facts about Vitamin C - Linda B. Bobroff; Isabel Valentín-Oquendo (EDIS, 2011)
Vitamin C, also known as ascorbic acid, has a wide variety of uses in the body. It helps slow down or prevent cell damage. It is needed to maintain healthy body tissues and the immune system. Vitamin C also helps our bodies absorb iron from plant foods. Learn the facts about this important vitamin with this revised 2-page fact sheet written by Linda B. Bobroff and Isabel Valentín-Oquendo and published by the UF Department of Family Youth and Community Sciences, December 2010.